Pengembangan Media Lift The Flap Book Untuk Mengenalkan Perilaku Hidup Bersih Dan Sehat Pada Anak Usia Dini: Studi Validasi Model Addie - Fatimah; Rahmi Sofyan; Rahmatun Nessa (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2026)
The implementation of Clean and Healthy Living Behaviors (PHBS) is very important for early childhood. In teaching, the conventional lecture method without interaction media causes the understanding of children aged 5-6 years to be less optimal. The ADDIE model Research and Development (R&D) research aims to develop the media lift the flap book "Let's Be a Healthy Child" to introduce four PHBS habits from the Directorate of Early Childhood Education. The data collection instrument uses validation sheets and questionnaires. The final validation results showed a very high level of validity: 94% (media experts) and 100% (Subject matter experts). Small group trials in three kindergartens in Banda Aceh and Aceh Besar gave positive results: Kindergarten Insan Tauhid Al Khair (100%), Taman An Nisa Kindergarten (77%) and Nurul Iman Kindergarten (87%). The development of this book has proven to be effective in increasing children's interest in reading. The results of this research can be implemented by educators to maximize the effectiveness of interactive health learning and become a theoretical basis for the development of similar media.